Comparison of porcine thorax to gelatine blocks for wound - Mabbott, A.; Carr, Debra J.; Champion, Stephen M.; Malbon, Christopher (Cranfield University, 2016)
Tissue simulants are typically used in ballistic testing as substitutes for biological tissues. Many simulants have been used, with gelatine amongst the most common. While two concentrations of gelatine (10 and 20 %) have been used extensively, no agreed standard exists for the preparation of either. Comparison of ballistic damage produced in both concentrations is lacking. The damage produced in gelatine is also questioned, with regards to what it would mean for specific areas of living tissue. The aim of the work discussed in this paper was to consider how damage caused by selected pistol and rifle ammunition varied in different simulants. Damage to gelatine blocks 10 and 20 % in concentration were tested with 9 mm Luger (9 × 19 full metal jacket; FMJ) rounds, while damage produced by .223 Remington (5.56 × 45 Federal Premium® Tactical® Bonded®) rounds to porcine thorax sections (skin, underlying tissue, ribs, lungs, ribs, underlying tissue, skin; backed by a block of 10 % gelatine) were compared to 10 and 20 % gelatine blocks. Results from the .223 Remington rifle round, which is one that typically expands on impact, revealed depths of penetration in the thorax arrangement were significantly different to 20 % gelatine, but not 10 % gelatine. The level of damage produced in the simulated thoraxes was smaller in scale to that witnessed in both gelatine concentrations,though greater debris was produced in the thoraxes.
Published online first in International Journal of Legal Medicine. The support of EPSRC and The Home Office are recognised. Open Access, this article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http:/ /creativecommons.org/licenses/by/4.0/)
Keywords: Tissue simulants; Gelatine; Wound ballistics; Ballistics; Wounds and injuries; Gunshot wounds